ChemInform Abstract: 24, 25‐Dihydrolimocinol, a new Triterpenoid from Fresh Fruits of Melia azadirachta. Issue 41 (October 2015) - Misra, Laxminarain; Gupta, Sonika; Sangwan, Rajender S.
Abstract isolation and structure elucidation of 24, 25‐dihydrolimocinol (I)